The role of viral infections in genesis of chronic esophagitis in children - E. I. Filjushkina; E. A. Kornienko; R. A. Nasyrov; T. B. Loboda (Журнал инфектологии)
The aim of this study was to reveal features of chronic viral esophagitis in children. 102 patients from 3 till 17 years with histologically confirmed chronic esophagitis (CE) are surveyed. Immunohistochemically viruses have been found in esophageal mucosa in 65 (64 %) children (1 group). 37 children (2 group) have CE of other causes. In 50 (77 %) children of 1 group HV have been revealed, in 22 (34 %) - CMV, in 19 (29 %) - VEB, in 22 (34 %) a combination of 2 or 3 viruses. Clinical manifestation of viral esophagitis was similar to reflux-esophagitis. Endoscopical signs of CE have been found in 55 % of children of 1 group and in 40,5% of 2 group, erosions were only in 1 group (15 %). The inflammatory index in 1 group was significantly higher, diskeratosis (14 %), parakeratosis (6 %) and balloon dystrophy (32 %) of esophageal epithelium were also revealed in it, but columnar metaplasia was not found. Thus, we have revealed high frequency of chronic virus infection as the cause of CE in immunocompetent patients. Erosions, higher degree of inflammatory changes morphologically and more manifest clinical symptoms are typical for a chronic virus esophagitis.